Analisis Faktor yang Mempengaruhi Tingkat Kesehatan Bank dengan Regresi Logit - Titik Aryati; Shirin Balafif (The Winners, 2007)
The article aims to find the probability effects of bank’s health level using CAMEL ratio analysis. The statistic method used to test on the research hypothesis was logit regression. The dependent variable used in this research was bank’s health level and independent variables were CAMEL financial ratios consisting of CAR, NPL, ROA, ROE, LDR, and NIM. The report data were extracted from bank’s financial from financial report, which had been published and accumulated by Infobank research bureau with valuation, based on bank Indonesia policy. The sample consisted of 60 healthy banks and 14 unhealthy banks in 2005 and 2006. The empirical result of this research indicates that the Non Performing Loan is the significant variable affecting bank health level.